HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG DISMINOREA DENGAN MOTIVASI UNTUK PERIKSA KE PELAYANAN KESEHATAN DI AKADEMI KEBIDANAN BUDI MULIA PALEMBANG - Y. Widyastuti Y. Widyastuti (STIKes Budi Mulia Sriwijaya, 2012)
ABSTRACT Disminorea as one of the symptoms that interfere with daily activities disminorea patient. But is often regarded as a minor without knowing disminorea can be caused by a gynecologic disorder that can affect infertility, pain,even death.The purpose of this study was to determine the relationship between knowledge about disminorea young women with the motivation to check into the health service at the Academy of Midwifery Budi Mulia Palembang in 2011.The research method used in this study is to survey the analytic approach to the Cross Sectional, the data obtained by using questionnaires that were distributed. The samples taken with a purposive sampling technique that is most students are experiencing at the Academy of Midwifery disminorea Budi Mulia Palembang by the number of samples of 82 people. The results of analysis of the 82 respondents found the level of knowledge of good responders were 42 respondents (51,2). The level of knowledge of respondents about 40 respondents (48,8%). Good level of motivation of respondents were 44 responden (53,7%) of respondents lacking motivation levels by 38 responden (46,3%). From the analysis of data showed no significant relationship between knowledge about disminorea teenage daughter with the motivation to check out. From the results of research to improve learning about in order to reduce the impact disminorea disminorea involved.. ABSTRAK Disminorea sebagai salah satu gejala yang mengganggu aktivitas sehari-hari penderitanya.Tetapi disminorea seringkali dianggap sebagai hal yang ringan tanpa mengetahui disminorea bisa disebabkan oleh kelainan ginekologik yang dapat mempengaruhi infertilitas, kesakitan, bahkan kematian. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan remaja putri tentang disminorea dengan motivasi untuk periksa ke pelayanan kesehatan di Akademi Kebidanan Budi Mulia Palembang Tahun 2011. Metode penelitian yang digunakan dalam penelitian ini adalah survey analitik dengan pendekatan secara Cross Sectional, data diperoleh dengan menggunakan kuisioner yang dibagikan. Sampel penelitian diambil dengan teknik purposive sampling yaitu sebagian mahasiswi yang mengalami disminorea di Akademi Kebidanan Budi Mulia Palembang dengan jumlah sampel 82 orang. Hasil analisa dari 82 orang responden didapatkan tingkat pengetahuan responden baik sebanyak 42 responden (51,2%). Tingkat pengetahuan responden kurang sebanyak 40 responden (48,8%). Tingkat motivasi responden baik sebanyak 44 responden (53,7%) tingkat motivasi responden kurang sebanyak 38 responden (46,3%). Dari hasil analisa data menunjukkan tidak ada hubungan yang bermakna antara pengetahuan remaja putri tentang disminorea dengan motivasi untuk periksa. Dari hasil penelitian untuk meningkatkan pembelajaran mengenai disminorea agar mengurangi dampak yang dilibatkan disminorea.